Experience and Philosophy - Manickam, Thomas (Journal of Dharma, 1999)
John B. Chethimattam Experience- and Philosophy. Bangalore : Dharmaram Publications, Dharmaram Vidya Kshetram, 1 996, pp.xii + 31 2, Rs. 360.OO;US$ 40.00.